The Effect of Limingtime and Bap Application on the Growth of Potato (Solanum tuberosum L.) Granola Varieties In Vitro Micro Sets - Meutia, Indah; Handayani, Rd. Selvy; Hafifah, Hafifah; Nilahayati, Nilahayati; Nasruddin, Nasruddin (Journal of Tropical Horticulture, 2022)
Potato is a horticultural plant that contains carbohydrates and nutrients. However, the problem faced in potato cultivation is the difficulty of obtaining high-quality tubers. Efforts that can be made to obtain healthy potato seeds are by propagating them using tissue culture techniques. The research aimed to determine the effect of the length of irradiation and application of BAP on the growth of granola potato micro cuttings in vitro. This research was conducted using a Split Plot Design (SPD) in a Completely Randomized Design (CRD) with two factors: length of irradiation (24-hour dark and 24-hour light) as the primary plot and BAP (0, 1, 2 mg/L) as sub-plots. Each treatment was performed in five replications. The results showed that the length of irradiation affected shoot growth time, number of roots (4-10 WAP), number of leaves (1-10 WAP), and shoot length (2-4 and 10 WAP). The best treatment was found in the 24-hour light treatment (L1). BAP treatment affected the percentage of growth success (9 and 10 WAP), root growth time, number of shoots (1, 4-10 WAP), number of roots (1-10 WAP), number of leaves (4-10 WAP), and shoot length (1-10 WAP).